Integrated Nutrient Management on Performance of Rice in Terraced Land - Dutta, Manoj; Sangtam, Roba (International Journal of Bio-resource and Stress Management, 2014)
Twelve treatments involving N, P and K (NPK) fertilizers, farmyard manure (FYM), poultry litter, forest litter, Azospirillum and Zn either alone or in combinations were applied continuously for ten years to evaluate the effect of integrated nutrient management practices on performance of upland rice in a terraced land. The plant height, numbers of tillers and productive tillers increased significantly in all the treatments whereas, grain yield increased significantly in all the treatments except ½N+PK and Forest litter burned+½ FYM over control. Among different nutrient management practices, NPK+Poultry litter produced maximum grain and straw yield. The grain yield in NPK+Poultry litter, NPK+FYM+Zn, NPK+FYM and NPK+Forest litter increased significantly (55.9, 45.7, 37.0 and 29.8%, respectively) as compared to addition of NPK alone. Increase in straw yield in different nutrient management practices ranged from 22.0 to 130.0%. The uptake of N, P and K was significantly higher in treatments where NPK was added with FYM and poultry litter. The average contribution towards apparent recovery of N, P and K from FYM was 36.4, 56.2 and 69.2%; from poultry litter 43.5, 27.7 and 85.9%; and from forest litter 80.4, 98.8 and 44.7%, respectively. After a decade of continuous cultivation, NPK+Poultry litter was found to be the best nutrient management practice that can be adopted for cultivation of upland rice on terraced land followed by NPK+FYM+Zn and NPK+FYM.